To evaluate the effects of an eight week Mindfulness Based Stress Reduction (MBSR) programme on quality of life in palliative care cancer patients - Lück, Patricia (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references (leaves 87-91).